The Determinants of Environmental Disclosure Quality: Empirical Evidence from Indonesia - Pricilia Angela; Sofik Handoyo (Journal of Accounting Auditing and Business, 2021)
Sustainability issues have increased the need for stakeholder toward environmental information disclosure. Quality of environmental information is pivotal for stakeholders to make a proper assessment of a firm’s environmental performance. This study examines the relationship between a firm’s characteristics and environmental disclosure quality. Firm’s characteristics in this study refer to the size, ownership concentration, age, and leverage. Content analysis of sustainability reporting was applied in this study. The study involved 33 listed firms in Indonesia Stock Exchange (IDX) that are consistently issued sustainability reporting during 2014-2016. Simultaneously test indicated that characteristics of the firm significantly explain the variance of environmental disclosure quality. However, partially test showed that leverage is the only variable significantly influenced environmental disclosure quality.